Perkembangan Kognitif Anak Usia Sekolah Dasar di SD Negeri Maguwoharjo 1 Depok Sleman - Farista Fitria Nurul Arfiani (Tafhim Al-'Ilmi, 2021)
AbstractThe cognitive development of children at elementary school age has several changes, includingchanges in mental abilities such as learning, reasoning, thinking, and language. The process thatoccurs and forms the structure needed to interact continuously with the environment, namely thestructure formed by intelligence, knowledge that is very subjective during infancy and childhoodand will become objective in adulthood. So it can be concluded that cognitive development inelementary school age children must always be adjusted to the learning ability and acceptance oflearning that occurs every day in students. Educators must also be good at adjusting the brainabilities of each individual student, so that material that is not in accordance with the students'brain abilities can damage the learning motivation and cognitive structure of students.Kata Kunci: Perkembangan, kognitif, Anak Usia Dini